Comparison of methods to assess onset of breast development in the LEGACY Girls Study: methodological considerations for studies of breast cancer - Lauren C. Houghton; Julia A. Knight; Mary Jane De Souza; Mandy Goldberg; Melissa L. White; Karen O’Toole; Wendy K. Chung; Angela R. Bradbury; Mary B. Daly; Irene L. Andrulis; Esther M. John; Saundra S. Buys; et al. (Breast Cancer Research, 2018)
Abstract Background Younger age at onset of breast development, which has been declining in recent decades, is associated with increased breast cancer risk independent of age at menarche. Given the need to study the drivers of these trends, it is essential to validate methods to assess breast onset that can be used in large-scale studies when direct clinical assessment of breast onset is not feasible. Methods Breast development is usually measured by Tanner stages (TSs), assessed either by physical examination or by mother’s report using a picture-based Sexual Maturation Scale (SMS). As an alternative, a mother-reported Pubertal Development Scale (PDS) without pictures has been used in some studies. We compared agreement of SMS and PDS with each other (n = 1022) and the accuracy of PDS with clinical TS as a gold standard for the subset of girls with this measure (n = 282) using the LEGACY cohort. We further compared prediction of breast onset using ROC curves and tested whether adding urinary estrone 1-glucuronide (E1G) improved the AUC. Results The agreement of PDS with SMS was high (kappa = 0.80). The sensitivity of PDS vs clinical TS was 86.6%. The AUCs for PDS alone and SMS alone were 0.88 and 0.79, respectively. Including E1G concentrations improved the AUC for both methods (0.91 and 0.86 for PDS and SMS, respectively). Conclusions The PDS without pictures is a highly accurate, sensitive, and specific method for assessing breast onset, especially in settings where clinical TS is not feasible. In addition, it is comparable to SMS methods with pictures and thus easier to implement in large-scale studies, particularly phone-based interviews where pictures may not be available. Urinary E1G can improve accuracy over than PDS or SMS alone.